Pangangalitawo a Subanen dance of love - Hofer, George P.; Deocampo, Nicolas Francisco A. (Quezon City University of the Philippines Diliman, 2025)
This study explores the question, "Who is the Filipino?" through an in-depth examination of the Subanen Tribe, one of the earliest indigenous groups in Zamboanga Sibugay.

Conducted by a filmmaker with ancestral ties to the region, the research emphasizes the richness of Subanen culture, particularly through the lens of their traditional wedding dance, which embodies their spirituality, connection to nature, and collective identity.

By documenting this vibrant ritual, the study reveals the Subanen way of life as a living testament to resilience and community, rather than a mere historical artifact.

The film situates the dance within the tribe's broader narrative, addressing their struggles and evolving identity in the face of marginalization.

This project serves as a bridge between past and present, tradition and modernity, and personal and collective belonging. It reflects the author's journey of cultural rediscovery and advocates for an inclusive understanding of Filipino identity that honors indigenous histories.

Ultimately, the research highlights the significance of reconnecting with ancestral heritage in shaping contemporary Filipino identity, aiming to inspire a renewed commitment to cultural inclusivity and historical awareness.
Thesis
Keywords: Pangangalitawo: a Subanen dance of love (Short film)